Messenger RNA recognition in Escherichia coli: a possible second site of interaction with 16S ribosomal RNA. - Petersen, G B (1988)
Examination of the nucleotides following the ATG or GTG initiation codons of a file of 251 genes from Escherichia coli has shown that 247 (98.4%) of them contain a sequence of at least three and 168 (66.9%) of them a sequence of at least four consecutive nucleotides that is complementary to some part of the 16 nt at the 5' terminus of the bacterial 16S rRNA. It is proposed that this sequence, which falls within the first 24 nt coding for the genetic message, might be involved in mRNA recognition through a mechanism analogous to the well-established 'Shine--Dalgarno' interaction with the 3' terminus of the 16S rRNA. Comparison of these data with data derived from a file of 117 'false' gene starts that have a Shine--Dalgarno-like sequence followed by a suitably spaced ATG or GTG triplet but which are believed not to lie at the beginnings of genetic messages shows the association that we have found to be statistically significant at the 99.9% level.